Marketing Managerial Coaching Tows Analysis And Food Poisoning Anticipation Training In Culinary Business: Coaching Manajerial Pemasaran Analisis Tows Dan Pelatihan Antisipasi Keracunan Makanan Pada Bisnis Kuliner - Sumartik; Hanum, Galuh Ratmana; Indayani, Lilik; Rachmawati, Errina; Gerung, Vido Michael (Procedia of Social Sciences and Humanities, 2022)
Problems The ability of Oiki Pizza SMEs in recognizing business strengths is felt to be lacking, threats and opportunities and business weaknesses for business sustainability are still not detected properly, the level of food health according to government standards is also not properly known in running its business. The solutions offered by the team proposing Abdimas Universitas Muhammadiyah Sidoarjo include assistance in Marketing Managerial Coaching in the form of training in the preparation of TOWS analysis (Threats, Opportunities, Weaknesses, Streghts). The method that the researcher uses is divided into 2 activities carried out from January 2022 to April February 2022, namely carrying out a TOWS analysis (Threats, Opportunities, Weaknesses, Streghts) including identifying the main TOWS issues and strategies implemented, and the next activity is food poisoning anticipation training for the first level. food health. The parties involved are the three proposing lecturers and two students who serve in the management study program, UKM Oiki Pizza. Abdimas' results, namely UKM Pizza Oiki were able to compile TOWS for their business activities and record food processing activities based on the health standards of the UNESCO World Health Organization to avoid food poisoning.